In vitro Study on the Flexural Strength of Different Polymethyl Methacrylate Denture Resins - Rajul Vivek; Alok Ranjan; Shaiq Gajdhar; Vaibhavi Parikshit Salunkhe; Smita Chaware; Vinay Rao (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Denture resins made of polymethyl methacrylate (PMMA) are often utilized because of their cost, aesthetic appeal, and simplicity of production. However, their mechanical characteristics, specifically, their flexural strength, are problematic, particularly when used in therapeutic settings for an extended period of time. The flexural strength of three PMMA denture resins that are sold commercially is assessed and contrasted in this research. Materials and Methods: In vitro tests were conducted on three different kinds of PMMA denture resins (Brands A, B, and C). By ISO 20795-1:2013 guidelines, 45 specimens (15 in each group) with measurements of 65 mm × 10 mm × 3 mm were created. To replicate oral circumstances, specimens were thermocyclically heated (5°C to 55°C) for 5,000 cycles after being polymerized in accordance with the manufacturer’s instructions. A universal testing machine was used to perform a three-point bending test at a crosshead speed of 5 mm/min to assess flexural strength. Flexural strength (MPa) was calculated by recording the maximal force at fracture. Tukey’s post-hoc test and one-way ANOVA were used for statistical analysis. Results: Brands A, B, and C have mean flexural strength values (±SD) of 65.3 ± 5.2 MPa, 72.5 ± 4.8 MPa, and 68.1 ± 6.0 MPa, respectively. The flexural strength of Brand B was substantially greater than that of Brands A and C (P < 0.05). But there was no discernible difference between Brands A and C (P > 0.05). Conclusion: In terms of mechanical durability, Brand B is a better option for denture bases since it showed the highest flexural strength among the evaluated materials. To assess other characteristics like impact strength and biocompatibility in clinical settings, further research is advised.